2020
DOI: 10.1002/emp2.12277
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in emergency medicine: A scoping review

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 73 publications
0
36
0
1
Order By: Relevance
“…One of the major challenges to bringing this work from the computer science laboratory to the bedside will be creating the interfaces necessary to implement it on the messy data of the real-time EHR. A review of the 20 most recently published studies cited by Kirubaranjan’s scoping review of AI in EM found that only one was implemented in the EHR, the rest performed on retrospective datasets exported for research [ 5 ]. As the work of EHR integration and data cleaning is as great or greater than writing ML algorithms, there is still a large gap between many published academic projects and their readiness for use in clinical practice.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major challenges to bringing this work from the computer science laboratory to the bedside will be creating the interfaces necessary to implement it on the messy data of the real-time EHR. A review of the 20 most recently published studies cited by Kirubaranjan’s scoping review of AI in EM found that only one was implemented in the EHR, the rest performed on retrospective datasets exported for research [ 5 ]. As the work of EHR integration and data cleaning is as great or greater than writing ML algorithms, there is still a large gap between many published academic projects and their readiness for use in clinical practice.…”
Section: Reviewmentioning
confidence: 99%
“…Although there are multiple prior papers using ML and AI in EM, including some recent reviews of the topic, few papers describe the basic concepts in a digestible format for emergency physicians without prior statistical or research backgrounds [ 5 ]. In this paper, we provide an introduction to the concepts of ML and precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…By addressing this research question, we complement related studies on AI in emergency care [ 12 , 13 ] with a distinct focus on why and how AI is used in emergency care and its effects on the work design of clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…More recently there have been scoping reviews of AI that have examined their use in aiding in medical diagnoses 27 and for clinical decision support. 28 Both reviews examined triage and unstructured narratives data, but they included these with disparate types of data.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, neither study referenced the previously mentioned systematic reviews, and both missed a significant number of studies identified in the systematic reviews that examined AI. Some of these omissions may have been intentional given that one review excluded studies that were linked to specific presentations (such as influenza, chest pain or trauma)28 or because the other review included only those that explicitly mentioned the use of synonyms for ‘artificial intelligence’ in their title, were not directly relevant to medicine (eg, public health) or ‘did not report outcomes or evaluations’ (eg, non-intervention epidemiological studies) 27…”
Section: Introductionmentioning
confidence: 99%